The Optimal Taxation of Risky Capital Income: The Rate of Return Allowance - Kevin Spiritus; Robin Boadway (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the optimality of taxing capital income according to a Rate-of-Return Allowance proposed by the Mirrlees Review. In a mean-variance framework the optimal tax on risk-free returns is zero with constant returns to scale in private investment, but positive with decreasing returns to scale, and vice versa. The optimal tax rate on excess returns to risky assets is positive if the stochastic tax revenue is returned to the household by variable public good provision. If it is returned as a stochastic lump sum, the optimal tax on excess returns is irrelevant with only aggregate risk, and approaches 100 % if there is also idiosyncratic risk.
Keywords: H21; H23; H24; 330; optimal capital taxation; rate of return allowance